The Development of LKPD Based on a Scientific Approach to Improve Students' Science Process Skills in Material on the Human Circulatory System and Digestive System Class XI SMA - Mia Ramayani; Violita; Abdul Razak; Muhyiatul Fadilah (Jurnal Penelitian Pendidikan IPA, 2024)
The development of Student Worksheets (LKPD) based on a scientific approach to material on the human circulation system and digestive system is based on the teaching materials used at SMA Negeri 16 Padang in the form of Student Worksheets (LKPD). The LKPD is not complete in terms of components or in terms of LKPD elements. The LKPD used only takes the form of sheets containing questions, and does not use an approach that contains activities or learning steps so that it cannot train students' science process skills. This research aims to produce LKPD based on a scientific approach to material on the human circulation system and digestive system that is valid, practical and effective to improve students' science process skills. This research is development research using the Plomp model which consists of three stages, namely preliminary research phase, development or prototyping phase and assessment phase.   The results of the LKPD validity test by the validator obtained a value of 84.67% with very valid criteria.   The results of the LKPD practicality test obtained a score of 90.74% by teachers and 88.30% by students with very practical criteria. The results of the T-test showed differences in values between the experimental and control classes with a significance of 0.000 each in the circulatory system and digestive system material. It can be concluded that LKPD based on a scientific approach is very valid, very practical and effective in improving science process skills.